The Influence of Service Quality and Customer Satisfaction on Customer Loyalty at Upgri Tour & Travel Semarang City - Cephas Sonny Hatmaja; Dr.Heri Prabowo,S.E., M.M; Dr.Bayu Kurniawan,S.Kom.,M.M (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research is about the effect of service quality and customer satisfaction on customer loyalty at UPGRI Tour & Travel Semarang City. This research using explanatory research involved 100 respondents selected through proportionate random sampling technique. Data was collected through questionnaires and analyzed using descriptive statistical analysis, validity and reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis testing coefficient of determination (R²), F test and T test. The results showed that service quality and customer satisfaction have a significant effect on customer loyalty. These findings suggest that these factors can increase customer loyalty and help companies create effective marketing strategies.